Gas permeation study of carbon tubular membrane by manipulating carbonization temperature profile - Wan Salleh, Wan Norharyati (2015)
Membrane-based separation technology has been widely applied for large-scale industrial CO2 capture due to its lower energy consumption and low pollutant production compared with other conventional techniques. The desirable properties in high performance gas separation membranes involve steps that must carefully be designed and controlled. This study investigates the role of carbonization temperature in the fabrication and performance analysis of carbon membranes prepared from polyimide. A commercial polyimide, Matrimid® 5218, was coated on the surface of ceramic tube to produce supported polymer membrane. The prepared polymer membrane was then carbonized under nitrogen atmosphere to produce supported carbon membrane for CO2/CH4 separation. The resulting carbon tubular membrane separation performance was evaluated using pure gas permeation test. Results showed that the suitable carbonization temperature for Matrimid-based carbon tubular membrane was at 850 °C. The highest selectivity for CO2/CH4 of 82.47 was obtained from carbon tubular membrane prepared at 850 °C.